Association of Calcium Supplementation During Pregnancy with the Birth Weight of Single-Born Neonates in Rural Northwest China. (29th May 2020) - Xiangyu, Gao; Baibing, Mi; Shaonong, Dang; Hong, Yan
Abstract: Objectives: To investigate the association of calcium supplementation during the pregnancy with the birth weight of single-born neonates. Methods: The survey employed a multistage, stratified and random sampling to investigate 15–49 aged pregnant women in 2010 to 2013 in Shaanxi province. A self - designed questionnaire was utilized. Birth weight between the 10(th) and 90(th) percentile was classified as appropriate for gestational age(AGA) infants. Chi-square test and logistic regression models were conducted to evaluate the association of calcium supplementation with single-born neonatal birth weight. Results: A total of 28, 490 women was enrolled in this study, 17 349 (60.9%) of participants had calcium supplementation during pregnancy. The incidence rates of small and large gestational age infants were 13.5% and 8.3%, respectively. The study conducted that calcium supplementation had a statistically significant difference in SGA (birth weight percentile <10) ( P < 0.01). After adjusting the regression models by confounding factors, we found that calcium supplementation was still protective towards SGA birth, the difference was statistically significant (OR = 0.89, 95% CI: 0.82–0.96, P < 0.05), but there was no significant difference in the birth to LGA (birth weight percentile <10). Conclusions: Calcium supplementation during pregnancy reduced the risk of SGA, but was not associated with the birth of LGA. Funding Sources: 1. Primary prevention and mechanisms of multi-micronutrient supplementation during periconception against congenital heart diseases: A community based randomised controlled trial in China (National Natural Science Foundation of China);